2011
DOI: 10.1073/pnas.1104030108
|View full text |Cite
|
Sign up to set email alerts
|

Processive phosphorylation of ERK MAP kinase in mammalian cells

Abstract: The mitogen-activated protein (MAP) kinase pathway is comprised of a three-tiered kinase cascade. The distributive kinetic mechanism of two-site MAP kinase phosphorylation inherently generates a nonlinear switch-like response. However, a linear graded response of MAP kinase has also been observed in mammalian cells, and its molecular mechanism remains unclear. To dissect these input-output behaviors, we quantitatively measured the kinetic parameters involved in the MEK (MAPK/ERK kinase)-ERK MAP kinase signalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
206
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(230 citation statements)
references
References 36 publications
21
206
0
Order By: Relevance
“…The second challenge is the gap between in vitro and in vivo studies, and the corresponding differences in parameter values. This is supported by evidence on the variation in parameter estimates between naive and crowded (physiological) in vitro molecular experiments (49,50). To gain insight into these complex systems described by complicated models, we must evade this parameter problem.…”
Section: Discussionmentioning
confidence: 99%
“…The second challenge is the gap between in vitro and in vivo studies, and the corresponding differences in parameter values. This is supported by evidence on the variation in parameter estimates between naive and crowded (physiological) in vitro molecular experiments (49,50). To gain insight into these complex systems described by complicated models, we must evade this parameter problem.…”
Section: Discussionmentioning
confidence: 99%
“…In essence, the experimental results of (9) and the numerical computations of (10) show that rapid enzyme-substrate rebindings can turn a distributive mechanism into a processive mechanism (so-called quasiprocessive). Based on these results, the authors of (10) argue for the importance of spatial models of such systems, despite the computational expense.…”
Section: Introductionmentioning
confidence: 99%
“…It can be observed that, in the case of slow diffusion, the more effective processive phosphorylation mode prevails over the less efficient distributive mechanism, boosting the system's activity [59,60]. Additionally, molecular crowding (and self-crowding), which is reflected explicitly in our lattice-based simulations and is expected to be significant at assumed surface densities of reacting molecules, facilitates consecutive phosphorylation events [61,62]. In the wellmixed approximation, kinases are dephosphorylated at the rate proportional to the product of phosphatase activity and the number of phosphatases.…”
Section: Discussionmentioning
confidence: 97%